2020
DOI: 10.1002/bit.27504
|View full text |Cite
|
Sign up to set email alerts
|

Wide‐surface pore microfiltration membrane drastically improves sieving decay in TFF‐based perfusion cell culture and streamline chromatography integration for continuous bioprocessing

Abstract: Although several compelling benefits for bioprocess intensification have been reported, the need for a streamlined integration of perfusion cultures with capture chromatography still remains unmet. Here, a robust solution is established by conducting tangential flow filtration-based perfusion with a wide-surface pore microfiltration membrane. The resulting integrated continuous bioprocess demonstrated negligible retention of antibody, DNA, and host cell proteins in the bioreactor with average sieving coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 32 publications
2
27
1
Order By: Relevance
“…In a recent study, Pinto and Brower 25 investigated the performance of the UJP and UMP microfilters for clarification during perfusion operations. They observed that the sieving coefficient for the smaller nominal pore size UMP microfilter was superior to the larger nominal pore size UJP microfilter.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Pinto and Brower 25 investigated the performance of the UJP and UMP microfilters for clarification during perfusion operations. They observed that the sieving coefficient for the smaller nominal pore size UMP microfilter was superior to the larger nominal pore size UJP microfilter.…”
Section: Discussionmentioning
confidence: 99%
“…Fully closed processing relied on using only peristaltic pumps and having the entire flow path being either gamma irradiated or autoclaved, including tubing, multi‐column BioSMB (Sartorius AG, Goettingen, Germany) manifold and Protein A columns. Aseptic techniques were employed for connections through tube welding with single use thermoplastic tubing (Pharmed L/S 16, Masterflex, PA) 18–20 . ProA FT was further processed via two different methods.…”
Section: Methodsmentioning
confidence: 99%
“…Performance comparison of ATF to TFF show a lower sieving decay for ATF, potentially due to the bidirectional flow, minimizing the biomaterial deposit on the hollow fiber membrane (Radoniqi et al, 2018; Wang et al, 2017). However the ATF has been associated with operational instability at higher cell densities (Pinto & Brower, 2020; Pinto et al 2020). Backflushing of the ATF and TFF filters with perfusate or fresh media has shown potential to extend filtration life during a manufacturing campaign (Wang et al, 2017; Wang et al, 2019).…”
Section: The Common Framework For Integrated and Continuous Manufactumentioning
confidence: 99%